Extrusion/spheronization of pectin-based formulations. I. Screening of important factors - Tho, Ingunn (Springer-Verlag, 2015)
This study investigated the possibility of producing pectin-based pellets by extrusion/spheronization. The study also identified factors influencing the process and the characteristics of the resulting product. Three types of pectin with different degrees of amid and methoxyl substitution were studied in combination with different granulation liquids (water, calcium chloride, citric acid, and ethanol) and/or microcrystalline cellulose. Pellets were prepared in a power-consumption-controlled, twinscrew extruder; then they were spheronized and dried. The products were characterized by image analysis, sieving analysis, and disintegration and dissolution tests. The results were evaluated by multivariate analysis. Different additives, either in the granulation liquid or in the powder mixture, influenced the ability of the extruded mass to form pellets (the processability) with this technique. However, the various pectin types responded to modifications to a different extent. Short, nearly spherical pellets are obtained with granulation liquids, such as ethanol, that reduce the swelling ability of pectin. Pellets produced with ethanol are, however, mechanically weak and tend to ditintegrate. Pectin molecules with a high degree of free carboxylic acid groups seem to be more sensitive to changes in the granulation liquid. Addition of microcrystalline cellulose as an extrusion aid generally resulted in improvements in shape and size. It was demonstrated that the processability of pectin as well as the characteristics of the products can be influenced in different ways during the process (eg, adding substances to the granulation liquid or to the powder mixture).